2016
DOI: 10.1097/bpo.0000000000000456
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionate Participation of Males and Females in Academic Pediatric Orthopaedics: An Analysis of Abstract Authorship at POSNA 2009-2013

Abstract: Female members of POSNA, in the most active part of their careers, participated at significantly lower rates than their male peers as accepted abstract authors for the 2009-2013 POSNA meetings than would be expected for their proportional size of total membership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The finding that women choose academic practice over private practice (in this survey, 13:1) is interesting in light of a recent study by Sharkey et al [12] that found that, when controlled for years of membership, women are less likely to present an abstract at the annual POSNA meeting. This suggests an extraordinary opportunity to develop more women leaders and role models at major pediatric orthopaedic centers.…”
Section: Discussionmentioning
confidence: 58%
“…The finding that women choose academic practice over private practice (in this survey, 13:1) is interesting in light of a recent study by Sharkey et al [12] that found that, when controlled for years of membership, women are less likely to present an abstract at the annual POSNA meeting. This suggests an extraordinary opportunity to develop more women leaders and role models at major pediatric orthopaedic centers.…”
Section: Discussionmentioning
confidence: 58%
“…For example, in the field of orthopedics, a specialty with a large gender gap, Sharkey et al found that female members of the Pediatric Orthopedic Society of North America (POSNA) had significantly fewer accepted abstracts and, therefore, lower academic participation in POSNA annual meetings compared with their male peers, and relative to their proportional representation in membership. 9 Similarly, a recent study found that women are underrepresented as presenters at European neurosurgical society conferences. 10 To our knowledge, the gender diversity of US neurosurgical conference abstract authorship has not been studied in detail.…”
mentioning
confidence: 96%
“…Successful publication is the "true currency" for academic promotion (1-6). There is still a lag, however, in participation of females in abstract authorship at recent POSNA meetings (32). After abstract authorship, the next step is manuscript publication; here the gender gap has been ubiquitously described (40).…”
Section: Discussionmentioning
confidence: 99%
“…al. (32) noted that females comprised 20.9% of candidate and active members of the Pediatric Orthopaedic Society of North America (POSNA). However, female members presented abstracts at a lower rate than males, suggesting females might be experiencing "barriers to academic participation".…”
mentioning
confidence: 99%